TANTANGAN SISTEM NOKEN DI PAPUA PEGUNUNGAN DALAM PERSPEKTIF ILMU SOSIAL DAN BUDAYA - Maya Andryani (Honeste Vivere, 2026)
General elections in the Papua Mountains region are known to use the noken system. The Noken system is a typical Papuan voting method based on customary deliberation, in which tribal chiefs or community leaders represent the community to cast votes, often using traditional "noken" bags as a symbol of mutual agreement. This is different from the context of general elections using their voting rights freely, honestly and fairly. Thus triggering election disputes due to potential fraud and theoretically violating the principle of direct elections with related problems 1) How is the Noken System in General Elections in Papua Mountains? 2) What are the challenges of implementing the noken system from the perspective of social and cultural discipline in accordance with the Constitutional Court Decision Number. 47-81 / PHPU.A-VII / 2009 and the General Election Commission Decision Number 1774 of 2024. The method applied in this legal research is a study of normative juridical research methods, which refers to substantive research from laws and regulations, books, journals and papers as well as other jurisprudence. The results, legal protection and legal certainty have a close relationship in the legal regulation of general elections in Papua Mountains with the noken system. Social and cultural science theory emphasizes the importance of the role of custom in the implementation of general elections in Papua Mountains. The Noken system has been legally recognized by the Constitutional Court Decision Number. 47-81/PHPU.A-VII/2009.